Strategi Manajemen dalam Meningkatkan Kualitas Pelayanan Pramusaji di Sky Light Rooftop Bar Kuta Beach Hotel - I Made Putra Mertha Sedana; Ni Nyoman Rusmiati; I.B. Nym Krisna Prawira Yuda (Ekodestinasi, 2026)
This study aims to analyze the management strategy in improving waiter service quality at Sky Light Rooftop Bar, Kuta Beach Hotel. The background of this research is based on fluctuations in guest visits and inconsistencies in service quality, which indicate that service standards have not been fully implemented optimally. This research uses a qualitative field research approach. Data were collected through observation, interviews, and documentation with Food and Beverage management staff. The data analysis technique used is descriptive qualitative analysis through data reduction, data presentation, and conclusion drawing. The results show that management has implemented several strategies such as training and development, daily briefing, and periodic performance evaluation. However, the implementation of these strategies is not yet fully consistent, especially during peak hours. Several obstacles were found, including limited product knowledge of waiters, inconsistency in SOP implementation, high workload during busy hours, and lack of utilization of guest feedback. Therefore, it can be concluded that waiter service quality at Sky Light Rooftop Bar is still in the development stage and requires more systematic and sustainable management improvement strategies.